ASPECTS REGARDING OVER-INDEBTEDNESS PREVENTION FOR VULNERABLE CONSUMERS - Apan, Rodica Diana (International Journal of Legal and Social Order, 2025)
Against the backdrop of national and european concerns for the prevention of over-indebtedness, this study aims to develop, among the procedures intended to help in this regard, the procedure established by banks for vulnerable consumers unable to execute the credit agreement. Two categories of consumers, considered vulnerable, are covered by this procedure, together with the Code of Conduct for banks, established at national level, namely, consumers in payment difficulties or representing a social case. The analysis of the principles governing the procedure, its effects on the relationship between the bank (creditor) and the consumer (debtor) in this stage, as well as a schematic guide, useful for facilitating its application by banks, are the theme of this study.